Resource-Driven Scheduling Implementation in Malaysian Construction Industry - Memon, Aftab Hameed; Mohammad Zin, Rosli (International Journal of Sustainable Construction Engineering and Technology, 2011)
Resource-driven scheduling techniques focus on resource. Their objective is to schedule activities so that a project dead line is met using predefined resource availability limits. This paper reports about the status of resource-driven scheduling implementation in Malaysian construction industry. An investigation Survey was conducted to determine the level of resource-driven scheduling and factors affecting the concerned implementation. Construction Firm registered under G7 (A Class), G6 (B class) and G5 (C class) were used in investigation. Data was analyzed by Statistical package SPSS to find the means and rank. Average index method was adapted to for the level of features of resource scheduling implementation and barrier to resource-driven scheduling. It is significant 59.65% firms are implementing resource-driven scheduling as partial. Also methods of project scheduling and resource options adopted were investigated. A Significant majority of construction firms (approximately 65%) adopt Microsoft project for scheduling. Study showed that the features of resource scheduling are being implemented at Medium Level. Lack of understanding / awareness of concepts, lack of genuine commitment, lack of coordination of key personnel and Lack of coordination of constructors consultants were found major factors that affect resource-driven scheduling. While, expensive to prepare is most contributing factor, no enforcement on schedules from authority, difficult to prepare and hurdles by personnel/authorities were found as major constraints in implementing resource driven scheduling.